Policy And Regulatory Impact On Educational Implementation (Study In The Kutai Kartanegara District Area) - Hairan Hairan; Bahari Joko Susilo; Aini, Aini (CV. AFDIFAL MAJU BERKAH, 2024)
This research will examine factors that are thought to influence the level of poverty in Kutai Kartanegara Regency, including, community income, education/literacy rates, employment/unemployment, and government policies. The research method used in this research is the empirical normative legal research method. The results of the research show that policies regarding education matters, apart from complying with statutory regulations, are also in the form of commitment from the Regional Head and Deputy Regional Head, namely the Regent and Deputy Regent of Kutai Kartanegara for the 2019 - 2024 period, must be implemented by the OPD in charge and have a strong legal umbrella. The justification for this program is not enough to include it in the Regional Regulation which regulates the RPJMD of Kutai Kartanegara Regency. The Kutai Kartanegara Regency Government's commitment to increasing human resources through education, especially formal education, is trying to set an education budget allocation of 20% of the APBD. Budgeting has been proven by Kutai Kartanegara Regency from 2019 to 2023. The budget allocation has exceeded 20% of the APBD. Basic education which is the authority of the Regency/City, Education Management, Curriculum, Educators and Education Personnel, Educational Licensing, Local Curriculum.